Wrist and Elbow Arthroscopy with Selected Open Procedures A Practical Surgical Guide to Techniques - Geissler, William B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Now in its revised and significantly expanded third edition, this comprehensive, authoritative text reinforces its standing as the gold standard on arthroscopic techniques for the wrist and elbow, now including selected open surgical techniques as well. Fundamental topics, such as anatomy, operative set-up, assessment, and lasers and electrothermal devices open the book. Generously illustrated with intraoperative photographs and full-color figures, chapters covering arthroscopic techniques are full-length and in detail. Topics include the management of TFCC tears, joint instability, arthritis, fractures and nonunions, dorsal and volar ganglions, and many more conditions and injuries of the wrist and elbow. While chapters on open techniques could present an extensive history and background of the subject as compared to the arthroscopic chapters, they will be focused approaches discussing why the author thinks it is the best open technique, including tips, tricks, pearls and how to perform the operation. Open management of ulnar impaction, scapholunate instability, total wrist arthroplasty, and elbow contractures are discussed, among others. Selected chapters include video supplements for additional, real-world demonstrations of techniques. Bringing together a truly international cross-section of experts and thought leaders in orthopedics and hand surgery, Wrist and Elbow Arthroscopy with Selected Open Procedures, Third Edition remains the premier resource for all clinicians working in this field.
Arthroscopic Wrist anatomy and Setup -- Evaluation of the Painful Wrist -- Lasers and Electrothermal Devices -- Anatomy of Triangular Fibrocartilage Complex -- Management of Type 1A TFCC Tears -- Management of Type 1B TFCC Tears: Whipple and Knotless -- Management of Type 1B TFCC Tears: Bone Tunnel Technique -- Management of Type 1B TFCC Tears: Anchor Technique -- Management of Type 1C TFCC Tears -- Management of Type 1D TFCC Tears -- Arthroscopic Management Ulna Impaction -- Open Management of Ulna Impaction -- Kinematics and Pathophysiology of Carpal Instability -- Arthroscopic Management of Scapholunate Instability -- Open Management of Scapholunate Instability -- Open Scapholunate Reconstruction with Fiber Tape Reconstruction -- Open Dorsal Capsulodesis for Scapholunate Instability -- Arthroscopic Management of Lunotriquetral Instability -- Arthroscopic Management of Dorsal Capsule Lesions -- Arthroscopic Management of Midcarpal Instability -- Arthroscopic Management of Trans-scaphoid Perilunate Dislocation -- Arthroscopic Management of Perilunate Dislocations -- Open Management of Perilunate Dislocations -- Wrist Arthritis Arthroscopic Techniques -- Arthroscopic Proximal Row Carpectomy -- Arthroscopic Partial Wrist Fusions -- The Art of Open Partial Wrist Fusions -- Open Total Wrist Arthroplasty -- Open Capitate Resurfacing -- Arthroscopic Arthrolysis -- Arthroscopic Management of Distal Radius Fractures -- Open Volar Plating for Distal Radius Fractures -- Open Dorsal Plating for Distal Radius Fractures -- Open Fragment Specific Plating for Distal Radius Fractures -- Arthroscopic Management of Scaphoid Fractures and Nonunions -- Open Plate Fixation for Scaphoid Fractures -- Vascularized Bone Grafting for Scaphoid Fractures -- Arthroscopic Assessment and Management of Kienbock$1 (Bs Disease -- Arthroscopic Excision of Dorsal Ganglions -- Arthroscopic Excision of Volar Ganglions -- Dry Arthroscopy and Its Applications -- Thumb CMC Arthroplasty within Trapeziectomy -- Arthroscopic Partial Trapeziectomy and Soft Tissue Interposition -- Open Suture-Button Suspensionplasty for the Treatment of Thumb Carpometacarpal Arthritis -- Open Fiber Tape Suspension with Trapeziectomy -- Open CMC Arthroplasty -- Small Joint Arthroscopy -- Endoscopic Carpal Tunnel Release -- Sports Injuries of the Hand and Wrist -- Complications of Wrist Arthroscopy -- Rehabilitation of Wrist Injuries -- Evaluation of the Painful Elbow -- Elbow Arthroscopy: Anatomy, Setup, Partials and Positioning -- Arthroscopic Management of Elbow Contractures -- Open Management of Elbow Contractures -- Arthroscopic Management of Lateral Epicondylitis -- Open Management of Lateral Epicondylitis -- Arthroscopic Management of Elbow Arthritis -- Total Elbow Arthroplasty -- Arthroscopic Management of Posterolateral Instability -- Open Management of Elbow Instability -- Arthroscopic Management of Osteochondritis Dissecans -- Arthroscopic Treatment of Elbow Fractures -- Open Management of Elbow Fractures Made Simple -- Radial Head Arthroplasty -- Endoscopic Ulnar Nerve Release -- Arthroscopic Ulnar Nerve Release -- Open Radial Tunnel Release -- Open Distal Biceps Repair -- Complications of Elbow Arthroscopy.s
Keywords: Orthopedics; Sports medicine; Orthopaedics; Sports Medicine; Wrist -- surgery; Elbow -- surgery; Arthroscopy -- methods